Diagnosis and prevalence of two new species of haplosporidians infecting shore crabs Carcinus maenas: Haplosporidium carcini n. sp., and H. cranc n. sp. Issue 11 (16th September 2020) - Davies, Charlotte E.; Bass, David; Ward, Georgia M.; Batista, Frederico M.; Malkin, Sophie H.; Thomas, Jessica E.; Bateman, Kelly; Feist, Stephen W.; Coates, Christopher J.; Rowley, Andrew F.
Abstract: This study provides a morphological and phylogenetic characterization of two novel species of the order Haplosporida ( Haplosporidium carcini n. sp., and H. cranc n. sp.) infecting the common shore crab Carcinus maenas collected at one location in Swansea Bay, South Wales, UK. Both parasites were observed in the haemolymph, gills and hepatopancreas. The prevalence of clinical infections (i.e. parasites seen directly in fresh haemolymph preparations) was low, at 1%, whereas subclinical levels, detected by polymerase chain reaction, were slightly higher at 2%. Although no spores were found in any of the infected crabs examined histologically ( n = 334), the morphology of monokaryotic and dikaryotic unicellular stages of the parasites enabled differentiation between the two new species. Phylogenetic analyses of the new species based on the small subunit (SSU) rDNA gene placed H. cranc in a clade of otherwise uncharacterized environmental sequences from marine samples, and H. carcini in a clade with other crustacean-associated lineages.